Wear-resistant and acid-alkali-resistant composite polishing pad and preparation method thereof
By using materials such as polyurethane resin and specific formulas in the polishing pad, the acid-base-resistant composite polishing pad is formed, which solves the problem of insufficient performance of the strong acid-base-resistant polishing pad in the semiconductor industry, and achieves efficient polishing effect and long-term use.
Patent Information
- Application Number
- CN202411551607.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-01
AI Technical Summary
It is difficult to develop high-precision, high-wear-resistant polishing pads that are resistant to strong acids and alkalis, especially in the semiconductor industry, there is a problem of insufficient material performance in the high-demand polishing process.
Using polyurethane resin, organic solvents, nonionic surfactants, rapid penetration agents, silicone oil defoaming agents and expandable plastic microspheres, a wear-resistant acid-base-resistant composite polishing pad is prepared through specific formulation and molding processes to form Open and closed-cell structures to improve the acid resistance and polishing efficiency of the material.
It improves the acid resistance and wear resistance of the material, reduces the accumulation of surface residues, improves the polishing quality and efficiency, and achieves good fit with high-demand components and long polishing cycles.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional polymer materials, and specifically relates to a wear-resistant acid-base resistant composite polishing pad and a preparation method thereof, which is mainly used for fine polishing of components such as silicon carbide substrates, sapphire substrates, ceramic substrates, and semiconductor films. Background Art
[0002] With the rapid development of the semiconductor industry, products have higher and higher requirements for chip density and precision, so substrates with higher precision, excellent surface flatness and extremely low friction coefficient are needed, and surface polishing technology is the key process to solve the surface quality problem of semiconductor wafers. The surface polishing process requires the use of materials such as polishing pads, polishing liquids and dressers, and among them, the polishing pad technology is the most difficult and the process control is the most complex. Its main functions in the polishing process include: ① effectively and evenly transporting the polishing liquid to different areas of the polishing pad; ② smoothly discharging the reactants and debris after polishing to achieve the removal effect; ③ maintaining a thin film of polishing liquid on the surface of the polishing pad so that the chemical reaction can be fully carried out; ④ keeping the polishing process stable and the surface non-deformed, so as to obtain a better wafer surface morphology. In order to fully meet these four requirements, polishing pads have also developed into a comprehensive category including polyurethane polishing pads, non-woven polishing pads, and fluff structure composite polishing pads. The research and development of fluff structure composite polishing pads is the most challenging. At present, China can only develop mid- and low-end products for this type of polishing pads. For polishing pads that need to be resistant to strong acids, alkalis, and oxidation, there are currently no successful cases in China. Summary of the invention
[0003] The purpose of the present invention is to propose a wear-resistant, acid-resistant and alkali-resistant composite polishing pad and a preparation method thereof, based on the fact that high-precision, wear-resistant and strong-acid and strong-alkali polishing pads are a blank field in China. The present invention can solve the polishing pad and process technology of such problems, and improve the comprehensive performance of the product by innovating in raw material formula and molding technology, so as to achieve the polishing quality of high-requirement components.
[0004] The technical scheme of the present invention is: a wear-resistant acid and alkali-resistant composite polishing pad, the composition and content of which are as follows by mass: 20-30 parts of polyurethane resin, 70-80 parts of organic solvent, 1-3 parts of non-ionic surfactant, 0.5-3 parts of rapid penetrant, 1-2 parts of silicone oil defoamer, 5-8 parts of filler, 3-7 parts of expandable plastic microspheres, and appropriate amount of pigment;
[0005] The polyurethane resin is prepared from the following raw materials in the following weight ratios, including 100 parts of polyester polyol, 31-49 parts of polymer polyol, 5.6-10.9 parts of low molecular weight polyol, and 43.3-55.5 parts of polyisocyanate;
[0006] The polyurethane resin preparation method is as follows:
[0007] 100 parts of the above-mentioned polyester polyol and 31-49 parts of polymer polyol by mass are slowly put into a three-necked flask filled with DMF at a temperature of 40-45° C., and after being stirred evenly, 43.3-55.5 parts of the above-mentioned polyisocyanate by mass are put into the three-necked flask, heated to 70° C. for reaction for 40-60 minutes, and then heated to 80° C. for reaction for two hours to obtain a prepolymer with an NCO content in the range of 3% to 5%, and then 5.6-10.9 parts of the low molecular weight polyol are added to adjust the skeleton and hard segment content of the polyurethane resin molecular chain so that the final polyurethane resin has an -NCO:-OH range of 1:1 to 1.05:1, and the reaction temperature of the prepolymerization process does not exceed 80° C. After the reaction is completed, degassing is carried out for half an hour, and nitrogen is filled for protection to obtain a polyurethane resin for standby use.
[0008] Furthermore, the polyester polyol is an aromatic polyester polyol and an aliphatic polyester polyol, with a relative molecular weight between 1000 and 2000 g / mol, an acid value less than 0.5 mgKOH / g, and a water content less than 0.05%.
[0009] Furthermore, the aliphatic polyester polyol is polybutylene adipate diol 1000.
[0010] Furthermore, the polymer polyols are POP H45, POP10 and POP13 produced by Dexin Federal Chemical Industry Co., Ltd.
[0011] Furthermore, the polyisocyanate is one or more of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI) or diphenylmethane diisocyanate oligomer.
[0012] Furthermore, the expandable plastic microspheres are 120DU15 or 120DU25 from POLYCHEM Corporation of the United States.
[0013] Furthermore, the organic solvent is selected from N,N-dimethylformamide or methyl ethyl ketone;
[0014] Furthermore, the silicone oil defoamer is selected from polyether siloxanes;
[0015] Furthermore, the nonionic surfactant is selected from fatty alcohol polyoxyethylene ether or fatty acid polyoxyethylene ester;
[0016] Furthermore, the rapid penetrant is selected from C90 or OEP-70;
[0017] Furthermore, the filler is one or more of polishing powders such as silicon dioxide, titanium dioxide, diamond powder, etc. with a particle size of ≤1 μm, wherein the particle size is preferably between 0.05-0.5 μm, and the color can be matched according to market requirements.
[0018] The preparation method of the wear-resistant acid-base resistant composite polishing pad of the present invention comprises the following steps:
[0019] Step (1) dissolving the prepared polyurethane resin in DMF to prepare a solution with a solid content of 20% to 30%, then adding 1 to 2 parts of a silicone oil defoamer, 1 to 3 parts of a nonionic surfactant, 0.5 to 3 parts of a rapid penetrant, an appropriate amount of pigment, and 3 to 7 parts of expandable plastic microspheres to the solution, mixing them thoroughly, controlling the viscosity at 3000 to 4000 mPa.s, and filling with nitrogen for protection to obtain a polyurethane resin solution for standby use;
[0020] Step (2) preparing a mixture of DMF and water at a DMF concentration of 15% to 20%;
[0021] Step (3) utilizes a conventional wet production process flow, adopts a scraping process to continuously scrape a layer of the polyurethane resin solution obtained in step (1) on the surface of the non-woven fabric, and slowly immerses it in the mixed solution obtained in step (2) at a temperature of 35 to 40° C., uses an ultrasonic displacement device to displace DMF in the polyurethane resin solution with water under the action of a silicone oil defoamer, a nonionic surfactant, and a fast penetrant, to form open-cell bubbles;
[0022] After the open-cell type bubbles of step (3) are solidified in step (4), they are washed and ironed again, and finally placed in an oven at a temperature of 135-140°C. The heat causes the expandable plastic microspheres to expand and foam, forming cavities and closed-cell structures inside. After the cavities and closed-cell structures are completely solidified, a wear-resistant, acid- and alkali-resistant composite polishing pad is obtained.
[0023] The present invention has the following advantages:
[0024] First, the acid resistance and wear resistance of the material are improved: the polyester polyol and polymer polyol (POP) used in the present invention are prepared by simultaneous prepolymerization (one-step method) with polyisocyanate (including diisocyanate), and a new type of polyurethane copolymer is obtained by this method, and the viscosity of the polyurethane resin is adjusted by adding low molecular weight polyol. The addition of POP can improve the strength and wear resistance of the product on the one hand, and on the other hand, it can partially improve the disadvantage of polyester polyol's inability to resist hydrolysis, improve the strength and acid and alkali resistance of the polishing material from a structural point of view, and then improve the wear resistance of the product.
[0025] Second, a new formula combination and molding structure is provided. By adding expandable microencapsulated plastic microspheres to the formula of the polyurethane resin solution, open and closed pores can be achieved at the same time. Water is used to replace the DMF in the polyurethane resin solution to form an open-pore structure. The open-pore structure can absorb polishing liquid and polishing residues, reduce surface residue accumulation, and cause quality problems of polishing elements. At the same time, through the drying process, the expandable plastic microspheres form closed pores at high temperatures, which improves the material's bearing capacity and adjusts the compression rate of the polishing pad, so that the polishing element and the polishing pad can fit perfectly, improving polishing efficiency and polishing quality.
[0026] Third, a process method for rapid replacement and formation of a microporous structure is provided: an ultrasonic device is used to co-frequency water substances, which are rapidly replaced under the action of silicone oil defoaming agent, non-ionic surfactant and rapid penetrant, to form a finger-like microporous structure with uniform distribution and fine pores. DETAILED DESCRIPTION
[0027] Embodiment 1:
[0028] Step 1: Preparation of polyurethane resin: 1000g of polybutylene adipate diol 1000 and 311.1g of polymer polyol POP H45 are respectively put into a three-necked bottle filled with DMF at a temperature of 40-45°C, and the temperature is strictly controlled not to exceed 60°C. After stirring evenly, 433g of MDI 100 is slowly added to the three-necked bottle, the temperature is raised to 70°C and reacted for 40-60 minutes, and the temperature is continued to be raised to 80°C and reacted for two hours to obtain a prepolymer with an NCO content of 3%. Then 500g of the prepolymer with a 3% NCO content is taken out, and 16.1g of 1,4-butanediol is added to adjust the skeleton and hard segment content of the polyurethane molecule so that the NCO:-OH range of the final polyurethane resin is 1:1. The reaction temperature of the prepolymer does not exceed 80°C throughout the whole process. After the reaction is completed, degassing is performed for half an hour, and nitrogen is filled for protection.
[0029] Step 2: Preparation method of polyurethane resin DMF solution: Take out 200g of the prepared polyurethane resin, dissolve it in 800g of DMF, stir evenly, then add 2% silicone oil defoamer, 1% S80, 0.5% fast penetrant, 5% 0.08 micron silica and 5% expandable plastic microspheres in sequence to make a polyurethane resin solution with a solid content of 20%, and control the viscosity at about 3000mps.a. After fully stirring, degas and set aside.
[0030] Step 3: Preparation of composite polishing pad: Place the pre-treated non-woven fabric horizontally on the coating machine, and then scrape the polyurethane resin solution on the surface of the non-woven fabric with a thickness of 1.3 microns. Then enter the pre-configured 15% DMF aqueous solution at a temperature of 35°C to fully complete the replacement process. Then put the non-woven fabric in a water tank to complete the final water washing. The concentration of DMF in the washing tank is controlled below 1%. Then it is ironed at high temperature and finally placed in an oven at 135°C for 40 minutes. On the one hand, it removes the remaining water and DMF, and on the other hand, it allows the expandable plastic microspheres to expand and foam to form a closed cavity to support it. After baking, it is cut and roughened to form the final composite polishing pad. After testing, the thickness of the polyurethane layer is 0.3 microns, the hardness is 66 Shore A, and the polishing roughness reaches 0.02nm. Under the action of PH13 polishing liquid containing potassium permanganate and mechanical polishing, the polishing cycle can reach 122h, during which no surface stratification or debris falling occurs.
[0031] Embodiment 2:
[0032] Step 1: Preparation of polyurethane resin: 1000g of polybutylene adipate diol 1000 and 311.1g of polymer polyol POP H45 are respectively put into a three-necked bottle filled with DMF at a temperature of 40-45°C, and the temperature is strictly controlled not to exceed 60°C. After stirring evenly, 433g of MDI 100 is slowly added to the three-necked bottle, the temperature is raised to 70°C and reacted for 40-60 minutes, and the temperature is continued to be raised to 80°C and reacted for two hours to obtain a prepolymer with an NCO content of 3%. Then 500g of the prepolymer with a 3% NCO content is taken out, and 16.1g of 1,4-butanediol is added to adjust the skeleton and hard segment content of the polyurethane molecule so that the NCO:-OH range of the final polyurethane resin is 1:1. The reaction temperature of the prepolymer does not exceed 80°C throughout the whole process. After the reaction is completed, degassing is performed for half an hour, and nitrogen is filled for protection.
[0033] Step 2: Preparation method of polyurethane resin DMF solution: Take out 200g of the prepared polyurethane resin, dissolve it in 466.6g of DMF, stir evenly, then add 1% silicone oil defoamer, 3% S80, 1.5% fast penetrant, 5% 0.08 micron silica and 7% expandable plastic microspheres in sequence to prepare a polyurethane resin solution with a solid content of 30%, and control the viscosity at about 3300mps.a. After fully stirring, degas and set aside.
[0034] Step 3: Preparation of composite polishing pad: Place the pre-treated non-woven fabric horizontally on the coating machine, and then coat the polyurethane resin solution on the surface of the non-woven fabric with a thickness of 1.3 microns. Then enter the pre-configured 15% DMF aqueous solution at a temperature of 40°C to fully complete the replacement process. Then put the non-woven fabric in a water tank to complete the final washing. The concentration of DMF in the washing tank is controlled below 1%. Then it is ironed at high temperature and finally placed in an oven at 135°C for 40 minutes. On the one hand, it removes the remaining water and DMF, and on the other hand, it allows the expandable plastic microspheres to expand and foam to form a closed cavity to support it. After baking, it is cut and roughened to form the final composite polishing pad. After testing, the polyurethane layer is 0.5 microns thick, the hardness is 68 Shore A, and the polishing roughness reaches 0.02nm. Under the action of PH13 polishing liquid containing potassium permanganate and mechanical polishing, the polishing cycle can reach 125h, during which no surface stratification or debris falling occurs.
[0035] Embodiment 3:
[0036] Step 1: Preparation of polyurethane resin: 1000g of polybutylene adipate diol 1000 and 311.1g of polymer polyol POP H45 are respectively put into a three-necked bottle filled with DMF at a temperature of 40-45°C, and the temperature is strictly controlled not to exceed 60°C. After stirring evenly, 555g of MDI 100 is slowly added to the three-necked bottle, the temperature is raised to 70°C and reacted for 40-60 minutes, and the temperature is continued to be raised to 80°C and reacted for two hours to obtain a prepolymer with an NCO content of 5%. Then, 500g of the prepolymer with a 5% NCO content is taken out, and 26.8g of 1,4-butanediol is added to adjust the skeleton and hard segment content of the polyurethane molecule, so that the NCO:-OH range of the final polyurethane resin is 1:1. The reaction temperature of the prepolymer does not exceed 80°C throughout the process. After the reaction is completed, degassing is performed for half an hour, and nitrogen is filled for protection.
[0037] Step 2: Preparation method of polyurethane resin DMF solution: Take out 200g of the prepared polyurethane resin, dissolve it in 466.6g of DMF, stir evenly, then add 1.5% silicone oil defoamer, 2% S80, 2.5% fast penetrant, 5% 0.08 micron silica and 7% expandable plastic microspheres in sequence to make a polyurethane resin solution with a solid content of 30%, and control the viscosity at about 3500mps.a. After fully stirring, degas and set aside.
[0038] Step 3: Preparation of composite polishing pad: Place the pre-treated non-woven fabric horizontally on the coating machine, and then coat the polyurethane resin solution on the surface of the non-woven fabric with a thickness of 1.5 microns. Then enter the pre-configured 15% DMF aqueous solution at a temperature of 40°C to fully complete the replacement process. Then put the non-woven fabric in a water tank to complete the final water washing. The concentration of DMF in the washing tank is controlled below 1%. Then it is ironed at high temperature and finally placed in an oven at 135°C for 40 minutes. On the one hand, it removes the remaining water and DMF, and on the other hand, it allows the expandable plastic microspheres to expand and foam to form a closed cavity to support it. After baking, it is cut and roughened to form the final composite polishing pad. After testing, the thickness of the polyurethane layer is 0.6 microns, the hardness is 72 Shore A, and the polishing roughness reaches 0.01nm. Under the action of PH13 polishing liquid containing potassium permanganate and mechanical polishing, the polishing cycle can reach 132h, during which no surface stratification or debris falling occurs.
[0039] Embodiment 4:
[0040] Step 1: Preparation of polyurethane resin: 1000g of polybutylene adipate diol 1000 and 311.1g of polymer polyol POP H45 are respectively put into a three-necked bottle filled with DMF at a temperature of 40-45°C, and the temperature is strictly controlled not to exceed 60°C. After stirring evenly, 555g of MDI 100 is slowly added to the three-necked bottle, the temperature is raised to 70°C and reacted for 40-60 minutes, and the temperature is continued to be raised to 80°C and reacted for two hours to obtain a prepolymer with an NCO content of 5%. Then, 500g of the prepolymer with a 5% NCO content is taken out, and 25.5g of 1,4-butanediol is added to adjust the skeleton and hard segment content of the polyurethane molecule, so that the NCO:-OH range of the final polyurethane resin is 1.05:1. The reaction temperature of the prepolymer does not exceed 80°C throughout the whole process. After the reaction is completed, degassing is performed for half an hour, and nitrogen is filled for protection.
[0041] Step 2: Preparation method of polyurethane resin DMF solution: Take out 200g of the prepared polyurethane resin, dissolve it in 466.6g of DMF, stir evenly, then add 3.5% silicone oil defoamer, 2% S80, 2% fast penetrant, 5% 0.08 micron silica and 4% expandable plastic microspheres in sequence to make a polyurethane resin solution with a solid content of 30%, and control the viscosity at about 4000mps.a. After fully stirring, degas and set aside.
[0042] Step 3: Preparation of composite polishing pad: Place the pre-treated non-woven fabric horizontally on the coating machine, and then coat the polyurethane resin solution on the surface of the non-woven fabric with a thickness of 1.5 microns. Then enter the pre-configured 20% DMF aqueous solution at a temperature of 40°C to fully complete the replacement process. Then put the non-woven fabric in a water tank to complete the final washing. The concentration of DMF in the washing tank is controlled below 1%. Then it is ironed at high temperature and finally placed in an oven at 140°C for 40 minutes. On the one hand, it removes the remaining water and DMF, and on the other hand, it allows the expandable plastic microspheres to expand and foam to form a closed cavity to support it. After baking, it is cut and roughened to form the final composite polishing pad. After testing, the thickness of the polyurethane layer is 0.5 microns, the hardness is 76 Shore A, and the polishing roughness reaches 0.03nm. Under the action of PH13 polishing liquid containing potassium permanganate and mechanical polishing, the polishing cycle can reach 128h, during which no surface stratification or debris falling occurs.
Claims
1. A wear-resistant, acid-resistant and alkali-resistant composite polishing pad, characterized in that: Its composition and content are as follows by mass: 20-30 parts of polyurethane resin, 70-80 parts of organic solvent, 1-3 parts of nonionic surfactant, 0.5-3 parts of rapid penetrant, 1-2 parts of silicone oil defoamer, 5-8 parts of filler, 3-7 parts of expandable plastic microspheres, and appropriate amount of pigment; The polyurethane resin is prepared from the following raw materials in the following weight ratios, including 100 parts of polyester polyol, 31-49 parts of polymer polyol, 5.6-10.9 parts of low molecular weight polyol, and 43.3-55.5 parts of polyisocyanate; The polyurethane resin preparation method is as follows: 100 parts of the above-mentioned polyester polyol and 31-49 parts of polymer polyol by mass are slowly put into a three-necked flask filled with DMF at a temperature of 40-45° C., and after being stirred evenly, 43.3-55.5 parts of the above-mentioned polyisocyanate by mass are put into the three-necked flask, heated to 70° C. for reaction for 40-60 minutes, and then heated to 80° C. for reaction for two hours to obtain a prepolymer with an NCO content in the range of 3% to 5%, and then 5.6-10.9 parts of the low molecular weight polyol are added to adjust the skeleton and hard segment content of the polyurethane resin molecular chain so that the final polyurethane resin has an -NCO:-OH range of 1:1 to 1.05:1, and the reaction temperature of the prepolymerization process does not exceed 80° C. After the reaction is completed, degassing is carried out for half an hour, and nitrogen is filled for protection to obtain a polyurethane resin for standby use.
2. The wear-resistant and acid- and alkali-resistant composite polishing pad according to claim 1, characterized in that: The polyester polyols are aromatic polyester polyols and aliphatic polyester polyols, with a relative molecular weight between 1000 and 2000 g / mol, an acid value less than 0.5 mgKOH / g, and a water content less than 0.05%.
3. The wear-resistant acid- and alkali-resistant composite polishing pad according to claim 2, characterized in that: The aliphatic polyester polyol is polybutylene adipate diol 1000.
4. The wear-resistant acid- and alkali-resistant composite polishing pad according to claim 1, characterized in that: The polymer polyols are POP H45, POP10 and POP13 produced by Dexin Federal Chemical Industry Co., Ltd.
5. The wear-resistant acid- and alkali-resistant composite polishing pad according to claim 1, characterized in that: The polyisocyanate is one or more of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI) or diphenylmethane diisocyanate oligomer.
6. The wear-resistant acid- and alkali-resistant composite polishing pad according to claim 1, characterized in that: The expandable plastic microspheres are 120DU15 or 120DU25 produced by POLYCHEM Company of the United States.
7. The wear-resistant acid- and alkali-resistant composite polishing pad according to claim 1, characterized in that: The organic solvent is selected from N,N-dimethylformamide or methyl ethyl ketone; The silicone oil defoamer is selected from polyether siloxanes; The nonionic surfactant is selected from fatty alcohol polyoxyethylene ether or fatty acid polyoxyethylene ester; The rapid penetrant is selected from C90 or OEP-70; The filler is one or more of polishing powders such as silicon dioxide, titanium dioxide, diamond powder, etc. with a particle size of ≤1 μm, wherein the particle size is preferably between 0.05-0.5 μm, and the color can be matched according to market requirements.
8. A method for preparing the wear-resistant, acid- and alkali-resistant composite polishing pad according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step (1) dissolving the prepared polyurethane resin in DMF to prepare a solution with a solid content of 20% to 30%, then adding 1 to 2 parts of a silicone oil defoamer, 1 to 3 parts of a nonionic surfactant, 0.5 to 3 parts of a rapid penetrant, an appropriate amount of pigment, and 3 to 7 parts of expandable plastic microspheres to the solution, mixing them thoroughly, controlling the viscosity at 3000 to 4000 mPa.s, and filling with nitrogen for protection to obtain a polyurethane resin solution for standby use; Step (2) preparing a mixture of DMF and water at a DMF concentration of 15% to 20%; Step (3) utilizes a conventional wet production process flow, adopts a scraping process to continuously scrape a layer of the polyurethane resin solution obtained in step (1) on the surface of the non-woven fabric, and slowly immerses it in the mixed solution obtained in step (2) at a temperature of 35 to 40° C., uses an ultrasonic displacement device to displace DMF in the polyurethane resin solution with water under the action of a silicone oil defoamer, a nonionic surfactant, and a fast penetrant, to form open-cell bubbles; After the open-cell type bubbles of step (3) are solidified in step (4), they are washed and ironed again, and finally placed in an oven at a temperature of 135-140°C. The heat causes the expandable plastic microspheres to expand and foam, forming cavities and closed-cell structures inside. After the cavities and closed-cell structures are completely solidified, a wear-resistant, acid- and alkali-resistant composite polishing pad is obtained.
Citation Information
Patent Citations
Polishing pad and method for producing the same
CN102152232A
Grinding pad for chemical mechanical grinding and preparation method thereof
CN113024768A
Polishing pad, method for manufacturing polishing pad, and method for polishing surface of optical material or semiconductor material
CN116761693A
Polyurethane non-woven fabric material and preparation method thereof
CN117779396A
Polishing pad base material and preparation method thereof
CN117924644A
